Acceptance and Protein Content of Skim Milk Avocado Velva with the Addition of Green Beans as an Alternative Snack for Stunting Toddler - Dhea Rifqiani Wahyudi; Taufiqurrahman Taufiqurrahman; Nur Hatijah; Nurul Hindaryani (Journal of Nutrition Explorations, 2025)
Stunting is a chronic malnutrition condition that occurs when food intake is insufficient and disease infections occur. This research aimed to identify the acceptability and protein content of Velva avocado skimmed milk with the addition of mung beans as an alternative snack for children to prevent stunting. This study is a true experimental with one control formula and two treatment formulas. Avocado Velva is made in a laboratory, and the hedonic test was conducted by 25 moderately trained panelists using color, taste, aroma, and texture indicators. Meanwhile, protein testing with Kjedahl Titrimetric method was carried out at the Saraswanti Indo Genetech Surabaya laboratory. The data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The most preferred formula was F1 (100 grams of avocado, 75 grams of skim milk, and 25 grams of mung beans). Provides a protein content of 2.96 g/recipe. A significant difference was found in texture (p=0.005). Protein content in F1 was highest at 2.96 g/recipe. The nutritional value and good acceptability of Velva F1 has the potential to be a nutritious snack alternative to help prevent stunting in children.